2022
DOI: 10.1039/d2cp00996j
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transitions, amorphization and alloying in Sb2S3

Abstract: Despite the extensive and systematic studies of pressure-induced phase transitions in sesqui-chalcogenides, several puzzles still remain to be solved. Here, the complicated phase transitions, amorphization, and alloying behaviors of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…81 Usually, about ten modes are clearly distinguishable. 20,21,26 The Raman spectrum of L-Sb 2 S 3 at 873 K appears to be reminiscent of its glassy counterpart, Fig. 4(d), except for a strong S-S stretching at 490 cm À1 .…”
Section: Nanocrystalline Sb 2 Smentioning
confidence: 94%
See 1 more Smart Citation
“…81 Usually, about ten modes are clearly distinguishable. 20,21,26 The Raman spectrum of L-Sb 2 S 3 at 873 K appears to be reminiscent of its glassy counterpart, Fig. 4(d), except for a strong S-S stretching at 490 cm À1 .…”
Section: Nanocrystalline Sb 2 Smentioning
confidence: 94%
“…The crystal structure of Sb 2 S 3 has been extensively studied both under ambient conditions [16][17][18] and under high pressure. [19][20][21][22][23][24][25][26] Nevertheless, the atomic structure of vitreous and liquid antimony sesquisulfide is largely unknown except for classical X-ray diffraction studies of glassy Sb 2 S 3 reported forty years ago and suffering from a limited accessible Q-range and insufficient r-space resolution. [27][28][29] In the case of PCM applications, [30][31][32] special attention should be paid to the origin of a high optical and electric contrast between the SET (crystalline) and RESET (amorphous) logic states since antimony sesquisulfide differs considerably from the benchmark telluride PCM (GeTe-Sb 2 Te 3 , GST, or doped Sb 2 Te) in both chemical bonding and local antimony environments.…”
Section: Introductionmentioning
confidence: 99%
“…53,67 The minor peaks around 240 and 330 cm −1 can be ascribed to the vibrations of B 2g and B 3g assigned modes. 53,67…”
Section: Resultsmentioning
confidence: 98%
“…The weak peaks around 100 cm −1 and major peaks near 70 cm −1 can be attributed to the A g assigned modes. 53,67 The peak around 170 cm −1 can be assigned to the B 1g assigned modes. 53,67 The minor peaks around 240 and 330 cm −1 can be ascribed to the vibrations of B 2g and B 3g assigned modes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation